Studies on Potential of Finger Millet (Eleusine Coracana Gaertn. L.) Amylases for Industrial Applications - Pande, Anita; Singh, Sobha; Samad, Jyoti; Saurabh, Kumar; Haider, Z.A (The International Journal of Biotechnology, 2015)
Amylases are of great significance especially in the food, brewing and detergent industry. An attempt has been made to study the characteristics of amylases produced during germination of finger millet (Eleusine coracana Gaertn. L.). Of the 25 genotypes studied RAU8 showed the maximum activity at pH 5 and temperature 60oC. This is the first report of optimum amylase activity at 60°C in finger millet. The best activity was observed in seeds geminated for 96 hours. The enzyme extract showed maximal activity till 90 minutes and 82.24% activity was retained even after 120 minutes. The thermostable character of the enzyme and retention of activity of the unprotected enzyme for 2 hours makes it suitable for industrial purposes. Further characterization of the different forms of the amylases may help in isolation of the most robust form which could then be cloned and expressed in microbes to enable large scale production for industrial purposes.